Assessing the roles of microbial agents and abiotic stressors in ponderosa pine dieback and mortality across the western United States - McKee, Michael D., author; Stewart, Jane E., advisor; Davis, Seth, committee member; Borowiec, Marek, committee member (Colorado State University. Libraries, 2025)
Ponderosa pine (Pinus ponderosa) is one of the oldest and most ecologically and economically important tree species in western North America. As the most widely distributed conifer on the continent, it plays a critical role in forest ecosystems and supports recreational, environmental, and commercial values. However, in recent years, increasing levels of dieback and mortality have been observed across its native range. These declines appear to be driven by a complex combination of biotic agents, such as fungal pathogens, and abiotic stressors like drought and heat. Abiotic conditions can weaken trees and increase their susceptibility to disease, but the specific causal agents behind this widespread dieback remain poorly understood. It is unclear whether the current landscape-level decline is primarily the result of one dominant factor or the consequence of multiple interacting stressors. The research presented in this thesis aims to address these gaps in knowledge by investigating the biotic and abiotic contributors to ponderosa pine decline. In Chapter 2, I present a multi-state field study conducted across regions of the western United States experiencing noticeable tree decline. This study assesses the prevalence of fungal pathogens and records abiotic stress conditions to determine their correlation with dieback and mortality. The overarching goal is to quantify ponderosa pine decline and evaluate how its drivers vary across different geographic regions. Specifically, this project addresses three key research questions: (1) What biotic and abiotic agents are contributing to dieback and mortality? (2) Is the prevalence and severity of disease observed sufficient to cause or contribute to significant dieback and/or mortality? (3) Are the pathogen drivers of mortality consistent across the western United States, or do they differ regionally? By answering these questions, the study will provide valuable insights into the patterns and drivers of ponderosa pine dieback and inform future monitoring and management strategies.